2009
DOI: 10.1371/journal.pone.0006073
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and Spatial Analysis of Clinical and Molecular Parameters in Dextran Sodium Sulfate Induced Colitis

Abstract: BackgroundInflammatory bowel diseases (IBD), including mainly ulcerative colitis (UC) and Crohn's disease (CD), are inflammatory disorders of the gastrointestinal tract caused by an interplay of genetic and environmental factors. Murine colitis model induced by Dextran Sulfate Sodium (DSS) is an animal model of IBD that is commonly used to address the pathogenesis of IBD as well as to test efficacy of therapies. In this study we systematically analyzed clinical parameters, histological changes, intestinal barr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

28
288
2
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 348 publications
(328 citation statements)
references
References 36 publications
28
288
2
5
Order By: Relevance
“…Consumption of DSS is known to impart histological changes in the colon, including an elevated damage severity score, lengthening of crypts and crypt loss [26], often in conjunction with significant shortening of the colon [31]. Crypt lengthening and crypt loss are also commonly observed indicators of DSS-induced colitis [32], however, only crypt loss was observed in the current study.…”
Section: Discussionmentioning
confidence: 62%
“…Consumption of DSS is known to impart histological changes in the colon, including an elevated damage severity score, lengthening of crypts and crypt loss [26], often in conjunction with significant shortening of the colon [31]. Crypt lengthening and crypt loss are also commonly observed indicators of DSS-induced colitis [32], however, only crypt loss was observed in the current study.…”
Section: Discussionmentioning
confidence: 62%
“…The outcomes in the DSS-colitis model can be effective in predicting clinical treatment of IBD [18]. It is well established that when DSS administration is halted, the animals will begin to spontaneously recover [50] and therefore differences among groups requires examining the temporal response. While only two markers for macrophage phenotype were used for immunolabeling, we chose the most representative marker of UC-like inflammation (TNF) and for M2-like macrophages (CD206).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we have shown that mice deficient in the macrophage-expressed C-type lectin SIGN-R1 have IBD may arise following a loss of barrier integrity and consequential activation of the innate immune system by exposure to the indigenous intestinal flora, evoking inflammation as a result of cell infiltration ofthe colon and resulting proinflammatory cytokine release (1). In the colitis model used in this study, DSS, a sulfated polymer, induces intestinal injury by a direct toxic effect on epithelial cells of the basal crypt, with a loss of integrity in the mucosal barrier allowing infiltration of intestinal bacteria (21). Subsequently, colon inflammation develops with an infiltration of macrophages, neutrophils, and eosinophils into the colon and increased production of the inflammatory cytokines IL-1b, TNF-a, and IL-6, which contribute to the inflammation and damage to the colon (21,31).…”
Section: Discussionmentioning
confidence: 99%